A difusão da filosofia lean construction no cenário da construção civil brasileira - Andrade, Ariane Pinheiro [UNESP]; Souza, Flavia Trofino de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The Lean Construction philosophy emerged from the industry success in adopting lean production concepts to the traditional model paradigms shift, adapting Toyota Production System techniques and tools to the building construction and management system. The Brazilian construction sector is marked by high production costs to reach its product, both in labor, equipment and materials. This scenario therefore becomes increasingly competitive, causing companies to look for alternatives that keep them live and active in the market, which justifies their interest in the Lean Construction philosophy use in processes. The following thesis presents the discussions, methods and results of an undergraduate level research, whose objectives are to identify the nuances and particularities from the application of lean philosophy concepts in the scenario of construction in selected construction sites. For this analysis, a qualitative questionnaire was developed in order to identify some aspects in the studied construction sites, which are defined by the philosophy defined by Lauri Koskela, that fit in the context of construction in her thesis: "Application of the new production philosophy to construction (1992)". From the analysis and discussion of the results, it was possible to achieve the objectives proposed with this thesis, identifying the diffusion level of lean construction in the construction scenario of 14 civil works in the state of São Paulo, as well as identify its advantages and disadvantages through a reference work in this philosophy. At last, one can visualize the difficulties encountered in its application, as well as the reason for its scarce diffusion in the country, having as reference the sample space of the civil works studied

A filosofia Lean Construction surgiu a partir do sucesso da indústria com a adoção dos conceitos da produção enxuta, com o objetivo de quebrar os paradigmas do modelo tradicional utilizado, de maneira a adaptar as técnicas e ferramentas do Sistema Toyota de Produção, ao sistema de construção e gestão de obras. O setor da construção civil brasileira caracteriza-se pelos elevados custos de sua produção para alcançar seu produto final, tanto com relação à mão de obra quanto a equipamentos e materiais. Este cenário torne-se, portanto, cada vez mais competitivo, fazendo com que as empresas busquem alternativas que as mantenham presentes e atuantes no mercado, o que justifica o interesse pelo uso da filosofia Lean Construction em seus processos. O trabalho a seguir apresenta as discussões, métodos e resultados de uma pesquisa de nível de graduação, cujo objetivo é identificar as nuances e particularidades da aplicação dos conceitos da filosofia Lean no cenário da construção civil em canteiros de obras selecionados. Para esta análise, foi desenvolvido um questionário de caráter qualitativo com o objetivo de identificar as características dos canteiros estudados, estes definidos pela filosofia que se adequam ao contexto da construção civil, definidos por Lauri Koskela, no trabalho Application of the new production philosophy to construction (1992). A partir das análises dos resultados, foi possível identificar o nível de difusão do conceito Lean no cenário da construção civil de 14 obras do estado de São Paulo, bem como identificar suas vantagens e desvantagens por meio de uma obra referência. Por fim, pode-se visualizar as dificuldades encontradas em sua aplicação e identificar o motivo de sua escassa difusão no país, tendo como referencial o espaço amostral das obras estudadas
The diffusion of the lean construction philosophy in the Brazilian civil construction scenario
Keywords: Lean construction; Construction site; Koskela principles; Construção enxuta; Canteiro de obras; Princípios de Koskela; Produção enxuta; Industria de construção civil